Synthesis and antibiofilm activity of 1,2,3-triazole-pyridine hybrids against methicillin-resistant Staphylococcus aureus (MRSA) - El Malah, Tamer; Soliman, Hanan A.; Hemdan, Bahaa A.; Abdel Mageid, Randa E.; Nour, Hany F. (New journal of chemistry, 2021)
Antibiotic-resistant bacteria are emerging at an alarming rate, posing a potential threat to human health. We synthesised alkyne-functionalised pyridines 3 and 4 via alkylation of substituted 2-oxo-1,2-dihydropyridine derivatives 1 and 2 with propargyl bromide in alkaline DMF. The reactions afforded the O -propagylated compounds 3 and 4 as the main products. Copper( i )-catalysed azide–alkyne cycloaddition of compounds 3 and 4 with aromatic azides furnishes compounds 11–22 . The chemical structures of the 1,2,3-triazole-pyridine hybrids 11–22 were fully verified using different spectroscopic tools, such as FT-IR, 1 H NMR, 13 C NMR, and 2D NMR. We evaluated in vitro antibacterial and antibiofilm activities of the 1,2,3-triazole-pyridine hybrids 11–22 against methicillin-resistant Staphylococcus aureus (MRSA) in both planktonic and sessile cells. Compounds 17 , 18 , and 21 exhibited promising growth inhibition activity against planktonic and sessile MRSA cells with IC 50 = 34.94, 37.91, and 43.88 μM, respectively. The antibiofilm activities of the new compounds were evaluated using Vancomycin (Van) as a standard reference drug (IC 50 186.0 μM).